PEMAHAMAN TERHADAP PERLINDUNGAN HAK CIPTA ATAS BUKU PADA MAHASISWA FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI MAKASSAR - Arsyad, susalti Nur (FAKULTAS HUKUM UM PAREPARE, 2020)
The research aimed at identifying the students understanding to the book in copyright protection, the factors that influence the students understanding to the book in copyright and improving the students understanding to the book in copyright protection. Kind of this research is qualitative description. The research used juridical empiricism approach that analyzed aspect of law related to the statue number 19 year 2002 about copyright and regulations that related to the statue and notice the phenomenon that happened to the students in faculty of social sciences that related with their understanding to the book in copyright protection. Whereas, data process and data analyze used qualitative analyze. The results of this research are: (1) The students understanding about the book copyright protection, so it can divide into four points, are the students know and followed the copyright statue, the students know but did not followed the copyright statue, the students did not know but followed the copyright statue and the students did not know and did not followed the copyright statue. (2) The factor that influence students understanding to the book in copyright protection, namely functional factor that from needed and experienced and personal factor or factors inherent of individual that had relation when to interpret the rule. (3) The effort are made for improved the understanding to the book in copyright protection with socialization and education, and synergy with other stakeholder in book utilization associated with the optimization the information technology in learning process.